Deslocamentos forçados femininos entre o cosmopolitismo e a hospitalidade: uma análise da condição da mulher refugiada no Brasil - Mariana Karla de Faria (2021)
The present work analyzes, from a Cosmopolitan perspective, a refugee woman's condition in the Brazilian reality, from Derrida’s and Spivack’s approach. Forced displacements present new outlines and characteristics in the 21st century and are constituted by multifaceted social, legal, economic and political components. The new situation driven by migratory crises, triggers several criticisms of the Nation-State, strengthens xenophobia, strict control of borders, encourages prejudice and "reaffirms" the criminalization of migratory movements, which implies the precarious reception of refugees and several violations of human rights. Faced with the humanitarian crisis of forced displacement of global proportions, it is noted that the stigma and prejudice arising from Brazilian society in relation to refugee women is a remarkable revelation, which implies in their greater vulnerability, as well as in the enormous difficulties in carrying out the Your rights. Thus, the concept of refuge was established - from the origin of the consolidation and analysis of national, regional and international legal protection granted to these defendants. In this context, based on the bibliographical analysis, the interface between refuge and gender and the need to understand the refugee woman is erected, under a cosmopolitan perspective and unconditional hospitality by Jacques Derrida. Furthermore, it was investigated the female subordinate proposed by Spivack and a refugee status in the country, as well as the geopolitical, socioeconomic and cultural factors that hide forced female displacements to Brazil. The methodology used in this research is inductive, as from the analysis of cases, narratives of forced displaced persons and data, the subalternization of refugee women in different spheres (economic, social, political and intellectual) is demonstrated, and the need for understanding their existence, based on Derrida's Ethics of Unconditional Hospitality.